SOME EXTERNAL FACTORS THAT INFLUENCE CONSUMER BEHAVIOUR FOR PURCHASING CIGARETTES ON THE BULGARIAN MARKET: SOME EXTERNAL FACTORS THAT INFLUENCE CONSUMER BEHAVIOUR FOR PURCHASING CIGARETTES ON THE BULGARIAN MARKET - Spasova, Veselina; Zhelev, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The purpose of the present research paper is to examine and analyze what factors influence consumer buying behaviour for purchasing cigarettes on the Bulgarian Market. The study is limited to within the Bulgarian Tobacco Market. The factors were divided into two main categories: internal and external influences. The research focuses on the external factors as Packaging, Product availability and exposure, Social Class, Groups, Income and Occupation.